Development Framework for Agro-Based Industries in Secondary Cities of Sindh Province, Pakistan: SWOT Analysis of Ten-Year Perspective and Medium-Term Development Framework Plans - Kalwar, Saima; Dali, Melasutra Md; Hassan, Norhaslina (MDPI, 2018)
The study intended to explore planning strategies gaps in ten-year perspective and medium-term development framework plans for agro-based industrial development in secondary cities of Sindh Province, Pakistan. Document review and key informant interviews survey techniques were used for data collection. A total of 30 interviews were conducted from agro-based officials. The SWOT analysis technique was applied for data analysis. The results revealed the weaknesses of high priority for textile and sugar industries, lack of planning strategies for agro-based development in secondary cities, dependency on federal government for development funds and absence of finances to implement plans. The threats were unavailability of strategic agro-based infrastructure facilities in secondary cities, centralized planning system, cross border threats such as the war in Afghanistan and migration of Afghan refugees, weak law and order situation and diversion of development budget for defense activities. The study suggests decentralization of powers and robust planning strategies in the development plans to strengthen secondary cities of Sindh Province economically.